Economic and management higher education system in Portugal: An exploratory study about the challenges setting by the new Bologna paradigm - Reis, E.; Roberto, J. A.; Saraiva, M. M.; Novas, J. L. C. (14th Annual International Conference on Advances in Management (ICAM 2007), 2007)
Aiming at the increase of mobility in Europe, the Bologna Process is being implemented so that, until 2010, it will be possible to apply a set of common principles to all higher education institutions of the adherent countries. This ambitious process is trying to answer to a several social questions and economic challenges, promoting at the quality of education, the research capacity and the employment of the graduates. With the main objective of investigating the implications of this new teaching/learning paradigm in the work market with respect to the economic and business courses, an inquiry process was carried out. This paper presents the preliminary results and discusses some of the conclusions extracted from the inquiry process. It is expectable that the results of the inquiry process may contribute to improve the understanding about this new social and organizational reality in Europe by the educational institutions, the employers and the graduates.